The Value of Incumbency in Heterogeneous Platforms - Gary Biglaiser; Jacques Crémer (Center for Economic Studies and ifo Institute (CESifo), 2016)
We study the dynamics of competition in a model with network effects, an incumbent and entry. We propose a new way of representing the strategic advantages of incumbency in a static model. We then embed this static analysis in a dynamic framework with heterogeneous consumers. We completely identify the conditions under which inefficient equilibria with two platforms will emerge at equilibrium; explore the reasons why these inefficient equilibria arise; and compute the profits of the incumbent when there is only one platform at equilibrium.
Keywords: L86; 330; network effect; network externalities; platforms